The Effect of Signaling Principle in Asmaul Husna Mobile App on Knowledge, Perceived Awareness and Perceived Motivation Among Muslim - Rosmani, Arifah Fasha; Abdul Mutalib, Ariffin; Sarif, Siti Mahfuzah (2018)
Signaling principle makes people learn better when cues that highlight important materials are added. Therefore, this study is carried out to determine the effect of the principle in asmaul husna mobile application among Muslim on knowledge and perceived awareness on the context and perceived motivation of the learning material. As a contribution to the body of knowledge, this study hybridizes Cognitive Theory of Multimedia Learning (CTML) with signaling principle. It will disclose the benefits of learning though mobile towards bridging theory to practice particularly in Islamic mobile application. The proposed design and development of Signaling Principle Mobile Application (SPMA) will assist multimedia practitioners or developers in designing and developing Islamic multimedia learning application particularly in educating Muslim in asmaul husna with the assimilation of Signaling Principle and Nielsen’s Design Guidelines. This study is classified into quantitative category and utilizes quasiexperimental approach using pre-test and post-test factorial design, and the design and development phase in this study will be governed by Alessi and Trollip Instructional Design Model.